Practical aspects of beef carcass traceability in commercial beef processing plants using an electronic identification system - J.R. Davis; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2002)
The use of an electronic identification (EID) system in slaughter facilities holds great potential as a tool for animal and carcass traceability, if used as part of a comprehensive carcass tracking system. However, the correct association of each carcass with its individual EID tag number may be hindered at several points during the slaughter process. For 2,994 cattle slaughtered in 14 lots and bearing buttontype, full duplex EID ear tags, 113 (3.92%) had non-functional tags, 16 (0.53%) had no tag, and 37 extra head were introduced accidentally into one of our lots. Of the 2,994 carcasses, 71 (2.37%) were railed out for further trimming, 8 (0.27%) were retained for further inspection, 3 (0.10%) were condemned, and 1 carcass fell from the rail. For the plant in which data were collected, the hot-carcass scale operator ultimately had the responsibility for assuring that lots of carcasses accurately represented lots of cattle slaughtered. Although the current systems in some plants may be adequate for cattle traded on a live basis, they may not insure exact matching of live animals and their respective carcasses.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Electronic identification; Traceability; Beef cattle; Beef carcasses